2015
DOI: 10.1007/s00299-015-1782-0
|View full text |Cite
|
Sign up to set email alerts
|

The advance of tomato disease-related microRNAs

Abstract: Tomato is a model plant for studying plant-pathogen interactions. As regulatory factors, microRNAs (miRNAs) have been widely identified and play crucial roles in tomato-pathogen interactions, including host defense and pathogen counter-defense. Here, the review summarizes the discoveries and highlights of miRNAs in tomato diseases. Roles of artificial miRNAs in disease resistance are further discussed. Hence, a better understanding of the contribution of miRNAs in tomato disease will shed light on strategies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 96 publications
2
5
0
Order By: Relevance
“…Here, via high-throughput sequencing, we found that 24 known and 7 novel miRNAs were significantly responsive to B. elliptica infection compared with their levels in the uninfected control. Among the differentially expressed miRNAs, the majority were downregulated under diseases stress, which is in accordance with findings in other species suffering biotic stress (Luo et al, 2015; Wang and Luan, 2015). For instance, including miR164, miR166, and miR168, the expression of these miRNAs were induced under Verticillium longisporum infection in Brassica napus (Shen et al, 2014), which were exhibit the same expression pattern in lily under B. elliptica -infection.…”
Section: Discussionsupporting
confidence: 88%
“…Here, via high-throughput sequencing, we found that 24 known and 7 novel miRNAs were significantly responsive to B. elliptica infection compared with their levels in the uninfected control. Among the differentially expressed miRNAs, the majority were downregulated under diseases stress, which is in accordance with findings in other species suffering biotic stress (Luo et al, 2015; Wang and Luan, 2015). For instance, including miR164, miR166, and miR168, the expression of these miRNAs were induced under Verticillium longisporum infection in Brassica napus (Shen et al, 2014), which were exhibit the same expression pattern in lily under B. elliptica -infection.…”
Section: Discussionsupporting
confidence: 88%
“…Differential miRNA expression analysis indicated that both conserved and Solanaceae-specific miRNAs were differentially regulated during Alternaria stress, which is analogous to observations with other plant–pathogen interaction studies 4 , 18 , 22 , 23 . Our stringent analysis demonstrated that majority of miRNAs were down-regulated upon Alternaria- stress.…”
Section: Discussionsupporting
confidence: 86%
“…Data from the present work also show significant changes in expression profiles of miRNAs controlling various classes of R genes including NLRs (TIR-NBS-LRR and CC-NBS-LRR), RLPs, and RLKs. Upon PVY infection, miR482, miR6022, miR6023, miR6024, and miR6027 families, known for targeting R genes in tomato [81][82][83], were found to be either up-or down-regulated in our libraries. Sly-miR6023 and sly-miR6024 were here validated as post-transcriptional regulators of Cf-9 and R1A-4, respectively.…”
Section: Discussionmentioning
confidence: 91%